1991
DOI: 10.1128/jb.173.11.3564-3572.1991
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella typhimurium mutants defective in flagellar filament regrowth and sequence similarity of FliI to F0F1, vacuolar, and archaebacterial ATPase subunits

Abstract: Many flagellar proteins are exported by a flagellum-specific export pathway. In an initial attempt to characterize the apparatus responsible for the process, we designed a simple assay to screen for mutants with export defects. Temperature-sensitive flagellar mutants of Salmonella typhimurium were grown at the permissive temperature (30°C), shifted to the restrictive temperature (42°C), and inspected in a light microscope. With the exception of switch mutants, they were fully motile. Next, cells grown at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
147
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(154 citation statements)
references
References 82 publications
7
147
0
Order By: Relevance
“…There are several lines of evidence suggesting that the export apparatus is localized to the basal structure (Vogler et al 1991;Fan et al 1997;Ohnishi et al 1997). A small dome with a dip found in the C ring, C rod, is a good candidate for the export apparatus (Katayama et al 1996).…”
Section: Flagellar Structurementioning
confidence: 99%
“…There are several lines of evidence suggesting that the export apparatus is localized to the basal structure (Vogler et al 1991;Fan et al 1997;Ohnishi et al 1997). A small dome with a dip found in the C ring, C rod, is a good candidate for the export apparatus (Katayama et al 1996).…”
Section: Flagellar Structurementioning
confidence: 99%
“…The subunits of the rod, hook, hook cap, hook-filament junction, filament and filament cap are thought to travel through a hollow channel in the nascent structure (Mimori et al, 1995;Morgan et al, 1995) and to assemble at its distal end (Iino, 1969;Emerson et al, 1970). The export apparatus was proposed to be at the base of the flagellum and to be assembled itself at an early stage of flagellar biosynthesis, probably after the assembly of the MS ring and switch complex Vogler et al, 1991;Kubori et al, 1997). There is little in the way of physical evidence for the presence of such an export machinery in the flagellar basal body.…”
Section: Introductionmentioning
confidence: 99%
“…There is little in the way of physical evidence for the presence of such an export machinery in the flagellar basal body. Filament assembly studies with mutants and sequence similarity to proteins in other type III systems have implicated several flagellar proteins in the export process: FlhA, FlhB, FliH, FliI, FliP, FliQ and FliR (Vogler et al, 1991;. Among them, FliI, which shows sequence similarity to the catalytic ␤-subunit of the F 0 F 1 proton-translocating ATP synthase (Vogler et al, 1991), was demonstrated to be an ATPase, presumably providing energy for the export process or possibly acting as a chaperone (Dreyfus et al, 1993;Fan and Macnab, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…1). Flagellar export is notably fast: in the early stages of filament growth flagellin is delivered at a rate of several 55 kDa subunits per second 5 .ATP hydrolysis by FliI was thought to provide the energy for export because mutations that delete or reduce the activity of FliI block flagellar synthesis at the stage of rod assembly 1,4,6 (Fig. 1).…”
mentioning
confidence: 99%
“…ATP hydrolysis by FliI was thought to provide the energy for export because mutations that delete or reduce the activity of FliI block flagellar synthesis at the stage of rod assembly 1, 4,6 (Fig. 1).…”
mentioning
confidence: 99%